Adoption, Safety, and Retreatment Rates of Prostatic Urethral Lift for Benign Prostatic Enlargement. Issue 2 (1st August 2021) - Gaffney, Christopher D.; Basourakos, Spyridon P.; Al Hussein Al Awamlh, Bashir; Wu, Xian; Cai, Peter Y.; Hijaz, Adonis; Jaeger, Irina; Lee, Richard K.; Shoag, Jonathan E.
Abstract : Purpose: Novel minimally invasive therapies like the prostatic urethral lift are among the many endoscopic options for the treatment of benign prostatic enlargement and lower urinary tract symptoms (BPE/LUTS). To further understand the relative uptake, complications and retreatment rates of contemporary endoscopic procedures for BPE/LUTS across diverse practice types, we performed a retrospective study of inpatient and ambulatory surgery encounters in the Premier Healthcare database. Materials and Methods: We included men who underwent endoscopic procedures for BPE/LUTS between 2000 and 2018. We determined the utilization of endoscopic therapies for BPE/LUTS, 30-day and 90-day readmission rates, and retreatment rate. Multivariable logistic regression was used to assess the association of procedure type with outcomes for the 3 most commonly performed procedures. Results: We identified 175, 150 men treated with endoscopic surgery for BPE/LUTS. The annual percent utilization of the prostatic urethral lift increased from <1% in 2014 to 10.4% in 2018. Compared to transurethral resection of the prostate and prostate photovaporization, prostatic urethral lift was associated with a lower odds of readmission at 30 (OR 0.58, p <0.01) and 90 (OR 0.55, p <0.01) days and a higher odds of retreatment within 2 years of followup (OR 1.78, p <0.01). Conclusions: Providers have rapidly adopted prostatic urethral lift which accounted for more than 1 in 10 endoscopic procedures captured for BPE/LUTS in 2018. Men treated with prostatic urethral lift are readmitted less within 30 and 90 days but are more likely to be retreated within 2 years of their index procedure as compared to men treated with transurethral resection of the prostate or prostate photovaporization.